Apparent Homozygosity of p.Phe508del in CFTR due to a Large Gene Deletion of Exons 4–11 - Vassos Neocleous; Panayiotis K. Yiallouros; George A. Tanteles; Constantina Costi; Maria Moutafi; Phivos Ioannou; Philippos C. Patsalis; Carolina Sismani; Leonidas A. Phylactou (Case Reports in Genetics)
We report a classic cystic fibrosis (CF) boy with a large deletion of exons 4–11 in the cystic fibrosis transmembrane conductance regulator (CFTR) gene on one allele and p.Phe508del in exon 10 on the second allele. Both parents of Georgian and Ukrainian background had no personal or family history of the disease. The initial molecular diagnostic investigation identified the patient as homozygous for the p.Phe508del and not compatible with his parent’s genetic status. The possibility of nonpaternity or uniparental disomy (UPD7) was investigated and excluded using microsatellite analysis of highly polymorphic markers on chromosome 7. Array-CGH was also performed on the patient and revealed a male profile with a subtle deletion within the CFTR gene on the long arm (q-arm) of chromosome 7 (7q31.2). The deletion was confirmed by MLPA extending from probe L02380 to probe L14978 (28.7 kb) and that was inherited from his father, while p.PheF508del was inherited from his mother. These data highlight the need for additional testing for large deletions in patients with apparent homozygosity for a mutated CFTR allele that do not match the carrier status of the parents. Not testing can lead to misdiagnosis and misinterpretation of mutation carrier status and the expected penetrance of the disorder.